Etika bisnis dan undang-undang anti monopoli: penangkal bisnis curang - Setiati Widihastuti (Universitas Negeri Yogyakarta, 2004)
The reality of business opportunity in New Order (ORBA) era gives only for certain businessman. The growth of private sector of during that period, in one hand be marked with biased policies lead to market distortion. In another hand, private sector of business was implication of the most of business practices unfairly. The phenomenon has been grown and supported by the connection, directly as well as indirectly, of between policy maker and businessman. this fact pushed the release of the prohibition of monopoly and unfair business practice namely UU No. 5 /1999. Relying upon merely this law to be effective in shopping monopoly, oligopoly as well as monopsony is unreal hope. Because of those practices was common among the businessman moral